Growth evaluation of pejerrey Odontesthes bonariensis (Pisces, Atherinopsidae) grown in floating cages on Lake Titicaca - Amaru Chambilla, Glicerio Reyes (2021)
The pejerrey, is a species introduced to Lake Titicaca from the continental waters of Argentina. The study was carried out at the Titicaca Trout Fishing Company, located in front of the city of Pomata, Puno Region, at an altitude of 3882 msnm. The objective of this study was to evaluate the growth of Odontesthes bonariensis from two batches (A and B) grown in Titicaca, Peru, in floating cages developed in 2018 and 2019. Silverside juveniles of 77.9 mm in length were used. average 120 days old, sowing a total of 8500 individuals (batch A = 5300 and batch B = 3200), from artificial spawning of broodstock confined in floating cages. After 360 days in batch A, a maximum total length of 230.0 ± 2.10 mm was achieved, total weight 80.0 ± 1.73 g, the feed conversion was found at 1.7 ± 1.39. In batch B, a maximum total length of 231.7 mm ± 2.70 was obtained, total weight 83.07 ± 1.67 g and the feed conversion factor was found at 1.3 ± 0.67. The feed used was commercial trout feed. It is concluded that the trials of silverside growth in floating cages in Lake Titicaca (Peru), presented encouraging results, showing that the fish tolerates the type of culture and could become an alternative for the development of aquaculture in the region.